Training Doctoral Students to Advance Health Equity Through Policy Leadership: An Overview of the Health Policy Research Scholars Program - Keshia M. Pollack Porter; Attia Goheer; Jessica Harrington; Shannon Frattaroli (Health Equity)
Health Policy Research Scholars (HPRS) is an innovative, equity-focused leadership program for doctoral students from marginalized backgrounds and identities. HPRS trains scholars from various disciplines to apply their research while engaging in policy to advance health equity. The HPRS logic model illustrates that training will lead to short-term changes including increased knowledge and skills; an interdisciplinary mindset; and increased sense of belonging, confidence, and self-awareness to advance health equity in the longterm. This article provides an overview of HPRS, including the logic model, curriculum, and implications for training doctoral students to become health equity leaders.